Comparison of ANKLE Brachial Index and Popliteal Brachial Index in Wifi Classification to Predict Major Amputation of Pad Patients at Dr. Cipto Mangunkusumo Hospital - Uneputty, Yulandri F.; Utama, Alexander Jayadi; Soemarko , Dewi S (Jurnal Locus Penelitian dan Pengabdian, 2025)
Peripheral Arterial Disease (PAD) can lead to lower extremity amputation. The WIfI (Wound, Ischemia, Foot Infection) classification is used to predict the risk of amputation, but the ischemic component is often assessed using the Ankle Brachial Index (ABI) which has limitations on non-compressible arteries. The Popliteal Brachial Index (PBI) is proposed as a more accurate alternative because the measurement location is more proximal and less affected by arterial calcification. The purpose of the study was to compare the predictive values of ABI and PBI in the classification of WIfI against the incidence of major amputation in PAD patients. This study is designed as a Diagnostic Test using medical record data of patients with a PAD diagnosis that meets the inclusion and exclusion criteria for admission to the Division of Vascular and Endovascular Surgery at Dr. Cipto Mangunkusumo Hospital in 2024 – 2025. The data were analyzed univariately to see the distribution of the characteristics of each variable, and bivariate analysis was performed using the ROC curve and the McNemar Test to assess the predictive accuracy. The ROC curve analysis for ABI showed an AUC of 0.786 with a p < 0.05 and a 95% IK (0.690-0.881). Meanwhile, the ROC curve for PBI shows an AUC of 0.76 with a p < 0.05 and an IK of 95% (0.66-0.86), and with  a cut-off  value of both of them of 0.5. The McNemar test of the two methods showed no significant difference. These results show that both methods have an equal level of accuracy in classifying amputation risk based on the WIfI system. There is no comparison between the ABI and PBI values based on the WIfI classification system as a predictor of major amputation in PAD patients at Dr. Cipto Mangunkusumo Hospital.